Measurement of the CKM angle γ using B± → DK± with D → K0Sπ+π−, K0SK+K− decays - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Falabella, A.; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Grünberg, Oliver; et al. (Journal of high energy physics, 2014)
Abstract: A binned Dalitz plot analysis ofB±→DK±decays, withD→K0Sπ+π−andD→K0SK+K−, is performed to measure the CP-violating observables x± and y±, which are sensitive to the Cabibbo-Kobayashi-Maskawa angleγ. The analysis exploits asample of proton-proton collision data corresponding to 3.0 fb−1collected by the LHCb experiment. Measurements from CLEO-c of the variation of the strong-interaction phaseof the D decay over the Dalitz plot are used as inputs. The values of the parameters arefound to be x+= (−7.7±2.4±1.0±0.4)×10−2,x−= (2.5±2.5±1.0±0.5)×10−2,y+= (−2.2±2.5±0.4±1.0)×10−2, andy−= (7.5±2.9±0.5±1.4)×10−2. The first,second, and third uncertainties are the statistical, the experimental systematic, and thatassociated with the precision of the strong-phase parameters. These are the most precisemeasurements of these observables and correspond toγ= (62+15−14)◦, with a second solution at γ→γ+ 180◦, and rB= 0.080+0.019−0.021, wherer B is the ratio between the suppressed and favoured B decay amplitudes.